Cohort study of neurocognitive functioning and adaptive behaviour in children and adolescents with Niemann‐Pick Disease type C1. (19th November 2015) - Thurm, Audrey; Farmer, Cristan; Farhat, Nicole Yanjanin; Wiggs, Edythe; Black, David; Porter, Forbes D
Abstract : Aim: To describe the neurocognitive and adaptive behavior profile of children and adolescents with Niemann–Pick Disease type C1 (NPC1), a rare genetic disease that frequently presents in childhood, with variable onset and symptom complex involving neurodegeneration. Method: Thirty‐eight participants (20 males, 18 females; mean age 8y 10mo, SD 4y 8mo, range 1–18y) with NPC1 were evaluated through a natural history protocol. Results: NPC1 severity was in the mild to moderate range for most participants. Cognitive scores ( n =32) ranged from very low to above average; about half of the participants exhibited a clinically significant advantage of Verbal IQ over Non‐verbal IQ. Adaptive behavior scores ( n =21) were generally in the borderline to impaired range. Longitudinal cognitive data ( n =19) suggested a pattern of decreasing scores over time. However, most participants remained at the same general level of functioning throughout the study. Interpretation: This study begins to systematically describe the neurocognitive phenotype of children and adolescents with NPC1, identifying heterogeneity and decline, aiding in understanding the natural history of the disease to plan treatment studies. What this paper adds: First standardized neurocognitive data from children and adolescents with Niemann–Pick Disease type C1 (NPC1). Significant impairment was common but not universal, and was associated with time since neurological onset. A pattern of gradual decline was observed in repeated assessments. Variability over time was common. Individual assessments should be interpreted with caution. This article is commented on by Berry‐Kravis on pages221–222 of this issue.